Safety of recycled plastics and textiles: Review on the detection, identification and safety assessment of contaminants. (January 2023) - Undas, Anna K.; Groenen, Marc; Peters, Ruud J.B.; van Leeuwen, Stefan P.J.
Abstract: In 2019, 368 mln tonnes of plastics were produced worldwide. Likewise, the textiles and apparel industry, with an annual revenue of 1.3 trillion USD in 2016, is one of the largest fast-growing industries. Sustainable use of resources forces the development of new plastic and textile recycling methods and implementation of the circular economy (reduce, reuse and recycle) concept. However, circular use of plastics and textiles could lead to the accumulation of a variety of contaminants in the recycled product. This paper first reviewed the origin and nature of potential hazards that arise from recycling processes of plastics and textiles. Next, we reviewed current analytical methods and safety assessment frameworks that could be adapted to detect and identify these contaminants. Various contaminants can end up in recycled plastic. Phthalates are formed during waste collection while flame retardants and heavy metals are introduced during the recycling process. Contaminants linked to textile recycling include; detergents, resistant coatings, flame retardants, plastics coatings, antibacterial and anti-mould agents, pesticides, dyes, volatile organic compounds and nanomaterials. However, information is limited and further research is required. Various techniques are available that have detected various compounds, However, standards have to be developed in order to identify these compounds. Furthermore, the techniques mentioned in this review cover a wide range of organic chemicals, but studies covering potential inorganic contamination in recycled materials are still missing. Finally, approaches like TTC and CoMSAS for risk assessment should be used for recycled plastic and textile materials. Graphical abstract: Image 1 Highlights: The database on contaminants in recycled plastic FCM is limited. Nearly no information on the safety of recycled textiles is available. Studies covering potential inorganic contamination in recycled materials are still missing. Approaches like TTC and CoMSAS for risk assessment should be used for recycled plastic and textile materials.